PENGARUH PDRB, PENDIDIKAN, PENGANGGURAN DAN JUMLAH PENDUDUK TERHADAP KEMISKINAN DI KOTA BANJARMASIN - MUHAMMAD RICKY DARMAWAN; RUSDIANSYAH RUSDIANSYAH (PPJP Universitas Lambung Mangkurat, 2019)
This study suggest the effect of gross regional domestic product, mean years school, open unemployment and population to the poverty line in Banjarmasin City in 2007-20l7. Poverty is one of the prob1ems in economic deve1opment. Therefore in this study measuring effect of poverty line and the factors that inf1uence it can be found in the solution and appropriate po1icies to overcome poverty in the city of Banjarmasin. The scope of this study covers the conditions of poverty in Banjarmasin City. By ana1yzing for 10 years. The ana1ytica1method used is the method of mu1tip1e 1inear regression ana1ysis. By using the R-Square Test (R2), Simu1taneous Test (F Test) and Individua1 Test (t Test). The resu1ts of the study inf1uence the gross regiona1 domestic product, the average lenght of shcool, the open unemployment rate and population toghether have a significant effect on poverty in Banjarmasin City.Keywords: Gdp, Education, Unemployement, Population